Elimination of mismatched imbalance vibration of active magnetic bearing system using full order sliding mode controller - Hussain, A. R.; Ahmad, M. N.; Yatim, Abdul Halim (School of Postgraduate Studies, UTM, 2006)
This paper deals with the method to eliminate the vibration inherited in Active Magnetic Bearing(AMB) System due to mass imbalance of the rotor. The imbalance generates variable frequencies of sinusoidal disturbance forces that causes vibration in the system. The mathematical model of the AMB system derived is represented in state variable form and it is also shown that the system suffers the mismatched condition due to this disturbance. The method proposed to overcome the vibration effect is based on full order sliding mode control. In the design process, firstly, a sliding surface is designed that ensures the system is robust to uncertainties once it slides on the surface. Then, a controller that guarantees the system reaches and maintain on the sliding surface is proposed in which Lyapunov stability condition is satisfied. Several simulation result are obtained to evaluate the proposed method. The results show that the proposed controller is able to eliminate the vibration and the robust stability is also achieved.